Fluent in Many: Navigating English Learning Through Multilingual Identities - Agis Andriani; Munadi, Khusni Gusti Nurhasan; Asri Siti Fatimah (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
Multilingual identity awareness refers to the ability to recognize and navigate multiple language and cultural identities. Multilingual identity awareness is also closely related to differentiated learning that is in accordance with what students need. Therefore, it is very important to know what factors can influence multilingual identity awareness in learning English as a foreign language. The purpose of this study was to explore what factors can influence multilingual identity awareness in learning English as a foreign language. Data collection uses semi-structured interview and the data analysis used thematic analysis. Based on the results of data analysis, researchers found that there are several factors that can influence multilingual identity awareness in learning English as a foreign language, including educational factors, course assignments, environment, family factors, loves into language, language use, personal challenges and achievements, cultural beliefs and learners’ beliefs. The themes that include these factors include: (1) Experience; (2) Social Factors; (3) Learners’ Attitude Towards Language. Therefore, researchers conclude that in the context of multilingual identity awareness, the above factors can appear in someone who is learning English as a foreign language. The implication of this study is to provide references and knowledge for students who are studying English as a foreign language that multilingual identity is an asset, not an obstacle. For further research, it is recommended to conduct research with wider and more diverse participants, more critical data analysis and wider participant diversity.